PENGARUH JENIS PELARUT TERHADAP KADAR SENYAWA METABOLIT SEKUNDER DAN AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT BATANG LINO (Grewia koordersiana Burret) - Pote, Lodowik Landi; Taek, Maximus M; Nadut, Anggelinus; Latumakulita, Gertreda (Akta Kimia Indonesia, 2024)
Abstract: The process of extracting secondary metabolite compounds from plants through extraction. One of factor that influences the success of extraction is the type of solvent used. This study aims to determine the effect of solvent type on the contents of secondary metabolite compounds and the antioxidant activity of Lino (G. koordersiana Burret) bark extract. This research began with taking lino bark samples, extraction, phytochemical screening, content analysis and antioxidant activity tests. The research results showed that the yields for ethanol, methanol, ethyl acetate and n-hexane extracts were 42.15%, 41.65%, 0.98% and 0.62%, respectively. The phytochemical test results of ethanol and methanol extracts contain alkaloids, flavonoids, phenolics, triterpenoids, saponins and tannins. Meanwhile, ethyl acetate extract contains phenolics, triterpenoids and tannins and n-hexane extract contains triterpenoids. The results of analysis of secondary metabolite on the contents for ethanol, methanol, ethyl acetate and n-hexane extracts showed different results. Antioxidant activity test results for each ethanol, methanol, ethyl acetate and n-hexane extract with different IC50 values. Antioxidant activity of ethanol, methanol and ethyl acetate extracts has antioxidant activity in the very strong category. Meanwhile, n-hexane extract has antioxidant activity in the inactive category. The results showed that the type of solvent affected the levels and antioxidant activity of secondary metabolite compounds from Lino (G. koordersiana Burret) extract.